2019
DOI: 10.1371/journal.pone.0221790
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic control among diabetic patients in Ethiopia: A systematic review and meta-analysis

Abstract: Introduction Ethiopia recorded the highest numbers of people with diabetes in Africa. It is not uncommon for diabetic patients to have poor glycemic control leading to a number of complications. The aim of this systematic review and meta-analysis is to evaluate the level of glycemic control among diabetic patients in Ethiopia by combining the studies from the existing literature. Materials and methods The Preferred Reporting Items for Systematic Reviews and Meta-Analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
68
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 43 publications
(166 reference statements)
9
68
1
Order By: Relevance
“…The observed magnitude of suboptimal glycemic control status in this study is comparable with previous related studies conducted among diabetic patients in southwest parts of Ethiopia [ 25 , 26 ]. The finding of this study is also similar to the result of a systematic review and meta-analysis study carried in Ethiopia [ 17 ] and Costa Rica [ 27 ]. On the other hand, the magnitude of glycemic control in the current study was higher than other related primary studies carried out in Ethiopia [ 18 , 28 , 29 ], Kenya [ 30 ], and Zambia [ 31 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The observed magnitude of suboptimal glycemic control status in this study is comparable with previous related studies conducted among diabetic patients in southwest parts of Ethiopia [ 25 , 26 ]. The finding of this study is also similar to the result of a systematic review and meta-analysis study carried in Ethiopia [ 17 ] and Costa Rica [ 27 ]. On the other hand, the magnitude of glycemic control in the current study was higher than other related primary studies carried out in Ethiopia [ 18 , 28 , 29 ], Kenya [ 30 ], and Zambia [ 31 ].…”
Section: Discussionsupporting
confidence: 90%
“…In Ethiopia, some studies, including a systematic review and meta-analysis, were conducted evaluating the status of glycemic control and some factors associated with it [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. The systematic review and meta-analysis determined suboptimal glycemic control to be about 76.8% in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…The obstacles to addressing diabetes in developing countries, particularly those in Sub-Saharan Africa, are a limited understanding of its prevalence, modifiable risk factors and complications arising from under-recognition and/or under-treatment [5]. Ethiopia has been found to have the highest number of people with diabetes in Africa, with an estimated 2.6 million people with diabetes [6].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, about 40.0-60.0% of patients with diabetes have poorly controlled blood glucose [10]. One study conducted in Sub-Saharan Africa showed that 74.0% of patients with diabetes had poor glycemic control [11] and that in Ethiopia specifically, a large proportion of patients with diabetes (65.6-66.8%) were not able to achieve good glycemic control [6]. Glycemic control remains a challenging task, with the majority of patients failing to achieve a good glycemic status.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, there were over 1.33 million diabetic cases in Ethiopia, giving a prevalence rate of 2.9% among people of 20-70 years of age [1]. Recent systemic review and metanalysis study on glycemic control in Ethiopia indicated that there is a high proportion of diabetic patients who were unable to achieve optimal glucose level, with no difference between T1DM and T2DM [9].…”
Section: Introductionmentioning
confidence: 99%